Well-being in doctoral students: Considerations for the academic community - Cornejo-Araya, Claudia A.; Gallardo-Lazo, Marcela E.; Salas , Gonzalo; Tapia-Parada, Carla; López-López , Wilson; Marsico, Giuseppina (Psychology Hub, 2024)
Undertaking doctoral studies is a highly demanding academic activity, so it is important that those who embark on this challenge can experience the process positively. This article aims to expose and reflect on the relevance of the well-being of doctoral students as a need that must be addressed by the doctoral programs and higher education institutions. Considerations that the academic community, especially in the Latin American context, must take into account for an adequate development and training process for doctoral students, should include elements beyond the academic aspects. Based on the literature, these considerations include the student’s relationship with their thesis supervisors, motherhood and family, the constant pressure to publish, and procrastination. Finally, some areas are included to consider possible interventions to benefit the well-being of doctoral students, and the need for further research in the area is emphasized.